Maize–soybean intensification alternatives for the Pampas - Monzón, Juan Pablo; Mercau, Jorge Luis; Andrade, José Francisco; Caviglia, Octavio; Cerrudo, Aníbal Alejandro; Cirilo, Alfredo Gabriel; Vega, Claudia Rosa Cecilia; Andrade, Fernando Hector; Calviño, P.A. (2018)
Cultivating multiple crops as a land use alternative could increase system productivity and sustainability, providing options to soybean monoculture for the Argentinean Pampas. This study evaluates the performance of maize–soybean in double crop, relay crop and intercrop across a wide range of water supply and length of growing season in the Pampas. It also assesses the effect of maize cycle length and maize and soybean prices on these intensification alternatives. A total of 16 experiments, 6 rainfed and 10 irrigated, were conducted at four INTA Research Stations during five growing seasons. Yield ranged from 4390 to 16,862 kg ha−1, for sole maize crops, and from 1884 to 5130 kg ha−1, for sole soybean crops. The intensification alternatives productivity, measured as the land equivalent ratio (LER), was associated to the length of the growing season and was higher than 1.00 in 100%, 86% and 61% of the cases for maize–soybean double crop, relay crop and intercrop, respectively. Maize grain yield in double crop was similar to that of sole maize crop, whereas soybean yield in double crop was reduced compared to that of sole soybean crop due to sowing date delay. Maize and soybean grain yields under relay crop and intercrop were lower than their respective sole crops. The intercrop increased soybean yield and decreased maize yield compared with relay crop. Yield of soybean in intercrop and relay crop increased when sown with short cycle length maize hybrids. Maize and soybean sole crop yields were positively correlated (P < 0.01, r = 0.82). However, a negative correlation was found between maize and soybean yields for intensification alternatives under irrigated conditions (P < 0.01, r = −0.68), but not under rainfed conditions. The intercropping alternatives under rainfed conditions could reduce farm risk, due to the similar economic results with soybean sole crop, and the lack of correlation between soybean and maize yields.